2019
DOI: 10.3390/molecules25010080
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Solubility of Terephthalic Acid in Ionic Liquids

Abstract: Low solubility of terephthalic acid in common solvents makes its industrial production very difficult and not environmentally benign. Ionic liquids are known for their extraordinary solvent properties, with capability to dissolve a wide variety of materials, from common solvents to cellulose, opening new possibilities to find more suitable solvents for terephthalic acid. This work presents studies on the solubility of terephthalic acid in ionic liquids, and demonstrates that terephthalic acid is soluble in ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 13 publications
0
14
0
1
Order By: Relevance
“…1-butyl-3-methylimidazolium acetate and 1-ethyl-3methylimidazolium diethylphosphate. 55,56 Afterwards the content of the flask is titrated with 0.5 N KOH solution to a phenolphthalein endpoint. 1 H-NMR and UV-VIS spectra of obtained TPA after degradation are shown in Appendix, Fig.…”
Section: Characterization Of Depolymerized Monomers and Pet Wastementioning
confidence: 99%
“…1-butyl-3-methylimidazolium acetate and 1-ethyl-3methylimidazolium diethylphosphate. 55,56 Afterwards the content of the flask is titrated with 0.5 N KOH solution to a phenolphthalein endpoint. 1 H-NMR and UV-VIS spectra of obtained TPA after degradation are shown in Appendix, Fig.…”
Section: Characterization Of Depolymerized Monomers and Pet Wastementioning
confidence: 99%
“…The bottom phase should consist of an ionic liquid and water, and the upper phase should be created by the ester and unreacted alcohol. We assumed, based on previous studies [14][15][16][17][18], that this system would overcome the equilibrium and obtain a product with a high yield.…”
Section: Resultsmentioning
confidence: 99%
“…The low solubility of terephthalic acid in common solvents makes its industrial production very difficult and not environmentally benign. In our previous work, the solubility of terephthalic acid in ionic liquids was studied, and the results showed that terephthalic acid is partially soluble in ionic liquids, such as 1-ethyl-3-methylimidazolium diethylphosphate, 1-butyl-3-methylimidazolium acetate, and dialkylimidazolium chlorides up to four times higher than in DMSO (20 g of terephtalic acid per 100 g DMSO at 25 • C) [14]. Even though the solubility of terephthalic acid increased in the ionic liquid, the problem was not entirely solved.…”
Section: Introductionmentioning
confidence: 99%
“…Terephthalate salts with cations such as Na + , K + , and NH 4 + are also soluble in water [8] . On the other hand, terephthalic acid (TPA), which is not a salt, is poorly soluble in water and alcohols, but soluble in dimethyl sulfoxide (DMSO) [9] . The crystal structure of TPA is closely packed by the π‐π interactions between the benzene rings, [10] preventing OH radicals from penetrating into the crystal.…”
Section: Introductionmentioning
confidence: 99%
“…[8] On the other hand, terephthalic acid (TPA), which is not a salt, is poorly soluble in water and alcohols, but soluble in dimethyl sulfoxide (DMSO). [9] The crystal structure of TPA is closely packed by the π-π interactions between the benzene rings, [10] preventing OH radicals from penetrating into the crystal. Thus, the reaction between OH radicals and terephthalic acid occurs only on the crystal surface, which leads to low production efficiency of HTA.…”
Section: Introductionmentioning
confidence: 99%